Richard Scarry's Best sing-along Mother Goose video ever! - Scarry, Richard; Eastman, Tony.; Weiss, Ellen; DeRosa, Rich.; Jumbo Pictures; Sony Wonder (Firm).; Random House Video (New York, N.Y. Sony Wonder Random House Home Video, 2002)
Huckle looks for his friend Lowly Worm through Mother Gooseland and meets many new friends. Sing along with classic nursery rhymes.
Based on books and characters created by Richard Scarry.
DVD, Dolby digital.
Closed captioned.
Keywords: Children's songs; Nursery rhymes; Children's films; Animated films; Video recordings for the hearing impaired